SDM Guru dan Tantangan Profesionalitas Masa Depan - Hartini, Sri (Widya Wacana: Jurnal Ilmiah, 2012)
ABSTRACTTeachers play important roles in the students success of learning to bring them to a bright future. Concerning their responsibilities, teachers must master four basic competencies: pedagogic competence, personal competence, social competence, and professionalism competence. By mastering theses competencies, teachers can conduct meaningful teaching learning activities to make fun class. Students also find that learning is simple, effective, and efficient.Â Keyword: Teachers' competences, future professionalism challenge. (challenge of professionalism)